2000
DOI: 10.1021/jo001106f
|View full text |Cite
|
Sign up to set email alerts
|

A Very Short Synthesis of Steroids from 1,3-Butadiene and Benzocyclobutenes

Abstract: Lewis acid mediated addition of 1,8-bis(trimethylsilyl)octa-2,6-diene (BISTRO) 1 to succinic anhydride led to spirolactone 2 [(+/-)-6,9-divinyl-1-oxaspiro[4.4]nonan-2-one]. Methoxycarbonylation followed by stereoselective alkylation by various benzocyclobutenes afforded the substituted benzocyclobutene steroid precursors 5. Thermolysis of 5 gave rise to steroids (+/-)-6 with a trans-anti-cis configuration in five steps and in a highly stereoselective manner. Modifications of the sequence allowed the preparatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…In 2001, Santelli et al [58] reported a short synthesis of steroids from 1,3-butadiene and benzocyclobutenes. As indicated above, this strategy involved the use of intramolecular cycloaddition of o-xylylenes to generate the BC ring system, which was developed by Oppolzer [39][40][41][42][43][44] and Kametani [45][46][47][48].…”
Section: First Synthesesmentioning
confidence: 99%
“…In 2001, Santelli et al [58] reported a short synthesis of steroids from 1,3-butadiene and benzocyclobutenes. As indicated above, this strategy involved the use of intramolecular cycloaddition of o-xylylenes to generate the BC ring system, which was developed by Oppolzer [39][40][41][42][43][44] and Kametani [45][46][47][48].…”
Section: First Synthesesmentioning
confidence: 99%
“…For related literature, see: Farona (1996); Kirchhoff & Bruza (1993); Michellys et al (2001); Nemeto & Fukumoto (1998); Zhang et al (2006).…”
Section: Related Literaturementioning
confidence: 99%
“…Data collection: DIFRAC (Gabe & White, 1993); cell refinement: DIFRAC; data reduction: NRCVAX (Gabe et al, 1989); program(s) used to solve structure: SHELXS97 (Sheldrick, 1997); program(s) used to refine structure: SHELXL97 (Sheldrick, 1997); molecular graphics: ORTEPIII (Burnett & Johnson, 1996); software used to prepare material for publication: SHELXL97 and PLATON (Spek, 2003). Benzocyclobutenes (BCBs) are important building blocks for new polymers and advanced materials (Nemeto & Fukumoto, 1998;Michellys et al, 2001). Most of the reported benzocyclobutene monomers in the literature are bis-BCBfunctionalized compounds owing to their highly crosslinked structure and their excellent properties such as the insolubility, low solvent pickup and good thermal stability (Farona, 1996;Zhang et al, 2006;Kirchhoff & Bruza, 1993).…”
Section: Refinementmentioning
confidence: 99%
“…Cyclobutarenes are a class of structurally unique bicarbocyclic molecules which show a wide spectrum of biological activity (Christophe et al, 1998; Sadana et al, 2003). Due to the thermodynamic stability associated with the aromatic system and the kinetic reactivity of the strained cyclobutene ring (Cava and Napier, 1956; Mehta and Kotha, 2001), these molecules behave as reliable and synthetically useful feedstocks (Christophe et al, 1998) and have been extensively applied in natural product syntheses (Funk and Vollhardt, 1977, 1979; Grieco et al, 1980; Taber et al, 1987; Nemoto et al, 1995; Michellys et al, 2001). With these contributions in mind, great efforts to establish synthetic protocols for cyclobutarene synthesis have been developed which include 1,4-elimination-cycloaddition of functionalized arenes (Gray et al, 1978; Schirch et al, 1979; Sekine et al, 1979; Lenihan and Shechter, 1994, 1998; Chou et al, 1995), Parham cyclization (Bradsher and Hunt, 1981; Buchwald et al, 1987a,b; Beak and Selling, 1989; Aidhen and Ahuja, 1992), photo-induced cycloadditions (Parham et al, 1976; Kaneko and Naito, 1979; Neckers and Wagenaar, 1981; Kaneko et al, 1982; Kanao et al, 1983; Sato et al, 1987; Hoffmann and Pete, 1996), thermal extrusion reactions (Toda et al, 1988; D'Andrea et al, 1990; Hickman et al, 1991; Shimada et al, 1993; Andersen et al, 1996; Craig et al, 1998), intramolecular addition of carbanions to benzynes (Bunnett and Skorcz, 1962; Krohn et al, 1978; Gowland and Durst, 1979), [2 + 2 + 2] cycloadditions of 1,5-hexadiyne (Peter and Vollhardt, 1977, 1984; Funk and Vollhardt, 1980; McNichols and Stang, 1992), ring expansion of cycloproparenes (Birch et al, 1964; Iskander and Stansfield, 1965; Buckland et al, 1987; Kagabu and Saito, 1988; Müller et al, 1989), and [2 + 2] cycloadditions of allene precursors (Inanaga et al, 1992; Ezcurra and Moore, 1993; Toda et al, 1994) and other methods (Markgraf et al, 1969; Garratt and Nicolaides, 1972, 1974; Bilyard et al, 1979; Warrener et al, 1993).…”
Section: Introductionmentioning
confidence: 99%